Expansion of Bruker Vertex 70v FTІR Spectrometer Capabilities - Zharkov, I.P.; Safronov, V.V.; Khodunov, V.O.; Konoval, V.M.; Maslov, V.O.; Selivanov, O.V.; Solonetsky, A.G.; Strelchuk, V.V.; Nikolenko, A.S.; Tsykaniuk, B.I.; Naseka, V.M. (Science and Innovation, 2024)
To expand the capabilities of VERTEX 70v Bruker spectrometer (Germany), a vacuumized L-type module attachment to the spectrometer has been designed and manufactured. The proposed configuration enables to mount and to adjust optical mirrors with a diameter of up to 50mm and to couple the attachment to cryostat with temperature control within the range from 2 to 330 K. The research has been carried out within the framework of instrument-making program of the NАS of Ukraine, grant # P-2/16-40.